Lições para o cortesão: ensinamentos práticos e morais nos tratados de duelo italianos do Século XVI - Queiroz, Victor Scire [UNIFESP] (2020)
This master thesis aims to analyze a set of treatises on the duel theme, produced in the Italic Peninsula of the 16th century. To this end, we will use the printed versions of this documentation, developed by the so-called professori d’onore, in addition with the works of jurists and moral philosophers, who in that period developed their theories of interpersonal combat. In an environment marked by greater social control by the Church and civil justice, these powers also acted to regulate the way the nobility resolved their tensions. In this new circumstance, we find the most varied reactions in the voices that were busy discussing issues related to a practice strictly linked to conflict and violence. Therefore, we intend to analyze not the legal or technical elements pertinent to the duel, but rather a whole set of lessons that sought a better way for courtly readers to live with their peers and stay in their positions. With this approach, we aim to understand the accommodation strategies formulated and indicated for readers to adapt to the greater social control present in these emerging courtship societies.